PATTERN OF ANTENATAL CARE PROVIDED AT A PUBLIC SECTOR HOSPITAL HYDERABAD SINDH - Nisar, Nighat; Amjad, Raheela (Journal of Ayub Medical College Abbottabad, 2007)
Background To assess the pattern of antenatal care provided to the pregnant women and to determine their level of satisfaction for provision of services. Methods: This cross-sectional study was conducted at a public sector hospital of Hyderabad Sindh, the data was collected in the month of October 2004. The data was collected by using a pre-tested semi-structured Questionnaire, during the month of October 2004. A total of 161 women consecutively attending antenatal care clinic were included in the study. The variables included were socio-demographic like age, education, occupation and income, maternal and child health variables and level of satisfaction about antenatal care provided. The data was analyzed by using statistical package SPSS version 11. Results: The mean age of women was 29.08ï‚±3.95 years, majority were housewife, 43.5% women were illiterate, 47.2% had primary education and 9.3% had secondary level of education. About 66% were from low-income group, i.e., earning less than 3000 rupees. About 71% were multi gravida, 67% had live births and 32% had history of abortions. Four had history of Intra uterine deaths. Only 22.4% reported that they use contraceptive for spacing. About 50% of the women were dissatisfied with the services available. The reasons identified for dissatisfaction were long waiting time, inadequate medicine supply and incomplete tetanus vaccination were also reported. Conclusion: This study concluded that antenatal care provided needs improvement and require attention to improve the quality of services provided. Key words: Antenatal care, quality of antenatal care, pattern of antenatal care